Physical Fitness and Depressive Symptoms during Army Basic Combat Training. Issue 1 (January 2015) - Crowley, Shannon K.; Wilkinson, Larrell L.; Wigfall, Lisa T.; Reynolds, Alexandria M.; Muraca, Stephanie T.; Glover, Saundra H.; Wooten, Nikki R.; Sui, Xuemei; Beets, Michael W.; Durstine, J. Larry; Newman-Norlund, Roger D.; Youngstedt, Shawn D.
ABSTRACT: Introduction: Mental health-related problems are a significant cause of attrition during basic combat training (BCT). Evidence in civilian populations suggests that physical fitness is associated with psychological benefits in civilians, but little is known about the association between physical fitness and psychological adjustment during BCT. Methods: This study prospectively examined the association between physical fitness and depressive symptoms in 300 BCT soldiers from May to July 2012 at Fort Jackson, Columbia, SC. Soldiers completed a baseline Army Physical Fitness Test (APFT) and survey within 1 wk of arriving at BCT and an end-of-cycle survey after 8 wk of BCT. Soldiers were assigned to the "high" fitness category if they had a passing score on the standard APFT of greater than or equal to 180 out of 300 points. Soldiers scoring less than 180 points on the APFT were assigned to the "low" fitness category. Depressive symptoms were measured using the 20-item Center for Epidemiologic Studies Depression scale. Results: In multivariate analyses, adjusting for baseline demographics, self-reported sleep before BCT, BCT confidence, Army identification, and depressive symptoms, the odds of reporting depressive symptoms were 60% lower for soldiers in the high fitness category (odds ratio, 0.40; 95% confidence interval, 0.19–0.84) compared with soldiers in the low fitness category. Conclusions: Analogous to other positive outcomes of soldier fitness, improvement of soldier physical fitness before BCT might improve soldiers' psychological health outcomes.